Phalaris canariensis L. (Poaceae): A new alien plant record for Kashmir Himalaya, India - Shugufta Rasheed; Anzar Ahmad Khuroo; Maroof Hamid; Aijaz Hassan Ganie; Akhtar Hussain Malik; Ghulam Hassan Dar (Journal of Asia-Pacific Biodiversity, 2016)
The correct taxonomic identification assumes first and foremost priority in the scientific documentation of biodiversity. The Kashmir Himalaya, located in the north-western side of the Himalayan biodiversity hotspot, is well-known for its diverse flora which merits immediate scientific documentation. In this context, the present study reports Phalaris canariensis L. (Poaceae) as a new alien plant record to the flora of Kashmir Himalaya, India. In this paper, a detailed description, photographs, and comparison of diagnostic characters with allied species are provided to scientifically validate this alien plant record for this Himalayan region.